2017
DOI: 10.1136/bmjopen-2016-015719
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ambulatory blood pressure variability and enlarged perivascular spaces: a cross-sectional study

Abstract: ObjectivesRecent studies reported that 24-hour ambulatory blood pressure variability (ABPV) was associated with lacunar infarction and white matter hyperintensities (WMH). However, the relationship between ABPV and enlarged perivascular spaces (EPVS) has not been investigated. Thus, our study aimed to investigate whether ABPV is associated with EPVS by 24-hour ambulatory blood pressure monitoring (ABPM).DesignWe conducted this study as a cross-sectional study.SettingsThe study was based on patients who present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…EPVS, also known as Virchow–Robin spaces, are most likely to be identified in T2-weighted MRI and are characterized by punctate or linear signal intensities similar to cerebrospinal fluids. [ 21 22 ]…”
Section: E Nlarged P Erivascular mentioning
confidence: 99%
See 1 more Smart Citation
“…EPVS, also known as Virchow–Robin spaces, are most likely to be identified in T2-weighted MRI and are characterized by punctate or linear signal intensities similar to cerebrospinal fluids. [ 21 22 ]…”
Section: E Nlarged P Erivascular mentioning
confidence: 99%
“…These results support the notion that EPVS in the BG may be a marker of CSVD. [ 22 28 ] The results of a prospective cohort study showed that WM-EPVS was associated with cerebral amyloid angiopathy (CAA) and superficial siderosis. [ 29 ] Conversely, a prospective, multicenter, hospital-based study published by Zhang et al .…”
Section: E Nlarged P Erivascular mentioning
confidence: 99%
“…However, previous studies have shown no association between BP and enlarged centrum semiovale PVS, probably due to differences in responsible pathogenetic mechanisms [12]. On the other hand, the strengths of this study include the population-based design and the unbiased selection of participants.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have confirmed that 24-h ambulatory blood pressure monitoring (ABPM) is more useful to predict the hypertension-related cardiovascular risk than casual clinical blood pressure measurement (9,10), and the 24-h blood pressure variability (BPV) documented by ABPM has been revealed an independent risk factor of the target organ damage caused by hypertension (11). Recent studies have found increased BPV correlates with white matter lesions, microbleed and enlarged perivascular space in the brain (12)(13)(14). The relationship of BPV and the total burden of cSVD has also been explored in some specific population lately (4,5,15), but the impact of BPV on the total cSVD burden has not yet been investigated in inpatients with cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 94%